LUIS DE VALDIVIA AND ALONSO MEJIA: A PERSONAL RELATION IN THE ORIGINS OF VALDIVIA’S THOUGHT (1602-1604) - Díaz Blanco, José Manuel; Gaune, Rafael (Revista de Historia Social y de las Mentalidades, 2015)
This study investigates the influence that Father Alonso Mejia could have had on the crucial intellectual change experienced by Father Luis de Valdivia in Lima between 1602 and 1604. To resolve the issue, it uses a comparative methodology, which intersects the biographies of both Jesuits and their most relevant writings in that regard: a memorial written by Mejía in 1603 and a report from Valdivia composed in 1604. The information that such analysis provides establishes the intellectual similarities between the two Fathers, as well as the biographical coincidences that brought them together, supporting the conclusion that, indeed, Mejia must have had a major influence in defining the political thought of Valdivia